Theoretical study of topological insulators : models and materials - Awadhesh, Narayan (Trinity College (Dublin, Ireland). School of Physics, 2014)
Topological insulators are a fascinating new class of materials, which have signalled a revival in exploration of topological aspects of condensecl matter physics. Like usual insulators they have an energy gap separating valence and conduction bands, however, their surfaces host metallic states which cannot be gapped out unless one breaks the symmetry protecting such surface states.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin